Coping with drought in irrigated South India: farmers' adjustments in Nagarjuna Sagar - Venot, Jean-Philippe; Ratna Reddy, V.; Umapathy, D. (Elsevier, 2010)
Continuous upstream water development in the South Indian Krishna Basin has resulted in declining water availability downstream. Upstream water use is not adjusted to reflect rainfall fluctuations, and downstream farmers of the Nagarjuna Sagar irrigation project in the state of Andhra Pradesh are increasingly vulnerable to water supply shocks. Understanding the adaptive capacity of irrigated command areas to fluctuating water conditions is critical. This paper documents the wide range of adjustments adopted by managers and farmers in Nagarjuna Sagar during a period of fluctuating water availability (2000-2007). Primary and secondary data indicate managerial adjustments such as rotational and timely water supplies to meet critical water demands of standing crops. Farmers responded to changing conditions through: (a) crop diversification, (b) shifting calendars, (c) conjunctive use, (d) suspending cultivation, (e) sale of livestock, (f) out-migration, and (g) tampering with the irrigation system. Adaptive strategies are more diverse in the tail-end than in the head-end of the canal network and local adjustments are often uncoordinated and may degrade the resource base. A better understanding of the practices induced by changes in water availability is needed to refine current water allocation and management in large surface irrigation projects. Crop diversification, deficit irrigation in low-flow years, and conjunctive use are some of the practices to be promoted in a conducive agricultural environment.